The impact of the Olympics on regular season team performance in the National Hockey League - Cairney, J.; Joshi, D.; Li, Y.-C.; Kwan, M. Y. W. (Journal of Athletic Enhancement, 2015)
Objective: The Winter Olympics occurs during the NHL regular season, and because many teams send multiple players to the Olympics, the question of whether there is a negative impact of player participation on team performance has been raised. In this paper, we examine the impact of player participation on goal differential for each Winter Olympic Games in the period from 1998 to 2014. Methods: Adjusting for prior team success (whether the team made the playoffs in the previous season), we test for a number of players by time (pre and post-Olympics) interaction in each season the Winter games occurred using mixed effects, growth curve modeling. Results: The results show a negative effect of player participation by time for the 1997-1998 NHL season: Teams with a higher number of players sent had more goals scored against them in the period after the Games than teams that sent fewer players. For the 2012 Winter Games, there is no effect of player participation on post-Games regular reason performance. The remaining seasons in which Olympic Games occurred shows a trend toward statistical significance (p<0.10). Conclusion: Possible explanations for these effects are discussed, as are limitations and future directions for research.